STATE OF THE ART AND LITERATURE REVIEW RESEARCH OF HOLLOW NANOFIBERS: FOCUSING ON FABRICATION, CAD IMPLEMENTATION AND OPTIMISATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The introduction of nanotechnology has resulted in a new era of materials research, with hollow nanofibers emerging as a key innovation. These nanofibers, distinguished by their nano size diameters and hollow structures, have generated significant interest due to their potential applications in a variety of industries. However, despite their advantageous properties, manufacture and analysis of these hollow nanofibers face significant challenges, particularly in terms of mechanical stability and structural integrity when subjected to external stresses. Identifying and addressing these vulnerabilities is crucial for the advancement of hollow nanofibers in various industrial and biomedical fields. The production of hollow nanofibers, notably via the electrospinning technique, has been the topic of a great deal of research. One of the bases of this research is the utilization of computer-aided analysis (CAD) simulations, which include techniques such as Representative Volume Element (RVE) analysis, Finite Element Method (FEM), multiscale analysis, numerical simulation, and optimization strategies. These sophisticated tools offer a magnified view into the nano-structural behaviour of hollow nanofibers, enabling precise predictions about their mechanical properties and behaviours under diverse conditions. This approach is revolutionary, as it allows for the exploration of theoretical and practical aspects of material behaviours without the constraints of traditional experimental methodologies. This article is in-depth scientific review on these theoretical and practical aspects.